Impact of Adjunctive Pharmacotherapy With Intragastric Balloons for the Treatment of Obesity. Issue 4 (April 2023) - Mehta, Amit; Shah, Shawn; Dawod, Enad; Hajifathalian, Kaveh; Kumar, Rekha; Igel, Leon I.; Saunders, Katherine H.; Kumbhari, Vivek; Farha, Jad; Badurdeen, Dilhana; Itani, Mohamad I.; Moore, Rachel L.; et al.
Background: We conducted this study to compare the weight loss outcome of intragastric balloons (IGBs) in conjunction with pharmacotherapy vs IGB and intensive lifestyle changes alone. Methods: This was a multicenter, non-randomized, retrospective study involving 4 academic hospitals. Patients underwent IGB placement with or without concomitant anti-obesity pharmacotherapy. The primary outcome was percent total weight loss (TBWL) after IGB placement at 6 and 12 months. Results: This study included 102 patients, with 23 patients (mean age 46.6 years, 82.6% female) treated with IGB/pharmacotherapy and 79 patients (mean age 46.0 years, 88.6% female) treated with IGB/lifestyle modifications. Patients had a 100% follow-up rate at 6 and 12 months. At 6 months following IGB placement, both groups achieved a similar %TBWL. At 12 months, %TBWL was greater in the IGB/pharmacotherapy group (12.6% ± 1.2 vs 9.7% ± 0.7, P = .04). 65.2% of patients achieved ≥10% TBWL at 12 months in the IGB/pharmacotherapy group, compared to 38.0% in the IGB/lifestyle group ( P < .05). The proportion of patients that achieved ≥15% weight loss at 12 months was also significantly different between the IGB/pharmacotherapy and IGB/lifestyle groups (30.4% vs 20.3%, P < .05). Discussion: IGB with concomitant use of pharmacotherapy did not improve weight loss while the IGB was in place compared to IGB and lifestyle changes. However, patients receiving IGB with pharmacotherapy did have greater weight loss and diminished weight regain after balloon removal compared to those receiving just IGB and lifestyle changes.